An Evaluation of Flipped Classroom Approach through Online System - Fitria Ramadhani Manurung (Darul Ilmi Bina Insan Foundation, 2025)
This qualitative research aims were to evaluate the effectiveness of implementing the flipped classroom model via online platforms and identify its strengths and limitations. Data collection involved classroom observations and interviews with an English instructor. Findings revealed that the educator successfully employed the flipped classroom method using digital tools like Google Classroom, WhatsApp, and email. Both the teacher and students experienced beneficial outcomes. The research identified several advantages and disadvantages of the flipped classroom for educators and learners. Key benefits included fostering student autonomy, encouraging self-directed learning, and supporting personalized education. Key benefits included fostering student autonomy, encouraging self-directed learning, and supporting personalized education. However, challenges included low student engagement, technical difficulties like poor connectivity, and restricted data access.